TESTING THE ACTIVITY OF THE N-HEXANE FRACTION OF THE ETHANOL EXTRACT OF BETTER BETTER LEAVES (Momordica Charantia L.) WITH VASELINE CARRIER ON THE HEALING OF CUT WOUNDS IN WHITE RATS (Rattus Norvegicus) - Lucky Andriani; Ivan Junius Mesak (Strada Journal of Pharmacy, 2020)
Wound are a form of damage to anatomical structure and function. When a wound occurs, the integrity of the epithelial structure of the skin is lost and dysfungtion occours in the skin. Therefore, normalization of integrity is required as soon as possible. Bitter melon leaves have benefits for wound healingand repairing skin granulation tissue. to understand the most optimal concentration level of N-Hexane Fraction of Bitter melon leaf ethanol extract in healing white rat incision wound using vaselin carrier and to understand the healing activity of N-Hexane fraction of Bitter melon leaf extract on white rat incision wound healing. The research conducted was an experimental type with the test animal, namely 18 white male rats. The white rats were grouped into 6 groups, where the standard control was group I, the positive control was group II with (injuring and giving sagestam cream) treatment, the negative control was group III with (injuring and giving it vaseline base) treatment, the last group IV, V, and VI were treated (injuring and giving it n-hexane fraction of bitter melon leaves at concentration levels of 1,5%, 3%, 6% and the base was vaseline).Then induced an incisions wound 2.0 cm deep and 0.2 cm long, but before shaving the rat’s back first and then anesthetizing using lidocaine injection. The observation process is carried out for 2 weeks and data collection is every 2 days. Furthermore, conduct statistical test when the data has been collected. Based on the results of observations and testing of the N-hexane fraction of bitter melon leaf ethanolextract, it has activity in healing cuts in white rats and the most optimal concentration in healing cuts is a concentration of 6%. The N-Hexane fraction of ethanol extract of bitter gourd leaves has activity in healing cuts in white rats and the most optimal concentration in healing cuts is 6%.